2015
DOI: 10.1177/1077801215591632
|View full text |Cite
|
Sign up to set email alerts
|

Familial Power and Women’s Contradictory Responses to Attitudinal Questions About Intimate Partner Violence in Rural Bangladesh

Abstract: Research is lacking on how power processes can influence women's reporting of their attitudes about intimate partner violence (IPV) against women. Structural elements of textual data were investigated as potential evidence of latent power. Overall, the majority of the women switched their response at least once throughout the interview, and the context of these contradictory responses provide evidence that women's reporting of attitudes about IPV against women may be understood as arising in part from latent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Komter (1989) proposed the concepts of manifest power and invisible power, where the manifest power concerns the visible outcomes of power in occasions such as open conflicts. This type of power is commonly seen in studies of family violence (Sato et al, 2015), workplace dispute (Edwards, 2006) and so on. When studying the conflicts on shared space for mobility, the manifest power could be interpreted as the differences in speed and size of the two parties.…”
Section: Dyadic Power Theorymentioning
confidence: 96%
“…Komter (1989) proposed the concepts of manifest power and invisible power, where the manifest power concerns the visible outcomes of power in occasions such as open conflicts. This type of power is commonly seen in studies of family violence (Sato et al, 2015), workplace dispute (Edwards, 2006) and so on. When studying the conflicts on shared space for mobility, the manifest power could be interpreted as the differences in speed and size of the two parties.…”
Section: Dyadic Power Theorymentioning
confidence: 96%
“…Even though gender norms can be either barriers or facilitators to equality (Connell , Connell and Pearse ), health promotion and international development actors tend to look mostly at harmful and discriminatory gender norms (Berkowitz , Elsenbroich and Gilbert 2014a, Harper and Marcus , Mehta and Gopalakrishnan , Pearse and Connell , Sato et al . , Temmerman , Usdin et al . ).…”
Section: Key Differences Between Social and Gender Normsmentioning
confidence: 99%
“…Often times the amount of dowry determines both a woman’s status in the family and the value of her opinion in the in-laws’ house, particularly in rural areas and urban slums [ 10 , 30 ]. However, a contradiction among women regarding IPV was observed by Sato et al, 2015 [ 31 ], who found that women tend to accept IPV in specific contexts, and these contexts contradict their general statement on IPV. Because of these ambiguities, we considered four specific contexts for spousal physical violence and women’s opinion of each.…”
Section: Introductionmentioning
confidence: 99%